Marbled Ware in Lágymányos (south of Aquincum) - Nagy, Alexandra (Rei Cretariae Romanae Fautorum Acta, 2022)
Among the almost 40 000 potsherds of the Lágymányos pottery workshop and indigenous settlement there are a few hundred marbled ware sherds. Their main forms are mostly terra sigillata imitations and transitional forms derived from late La Tène Period vessels. Although the forms and patterns of the vessels show various styles and techniques, they are also similar to other products from Pannonia or from some regions in the provinces of Germania and Moesia. The patterns are striped or mottled and the red decoration on the yellow slip was applied with sponge or different types of brushes. The suggested date of production is the end of the 1st century–beginning of the 2nd century AD. This workshop illustrates perfectly the transition from the late La Tène Period to the period of Romanization, trying to give some Roman character to their manufacture, although the mechanism for the adaption of the Roman vessels is not yet clear.